Children with Upper Airway Dysfunction: At Risk of Obstructive Sleep Apnea - Sisniega, Carlos; Katwa, Umakanth (Journal of Child Science, 2019)
Obstructive sleep apnea is characterized by prolonged partial upper airway obstruction or intermittent complete obstruction that disrupts normal ventilation during sleep and alters normal sleep patterns. Patients with obstructive sleep apnea tend to develop neurocognitive, cardiovascular, behavioral, attention issues, and poor academic performance. Therefore, it is essential to diagnose and treat obstructive sleep apnea early and avoid significant and long-lasting adverse outcomes. Most commonly, upper airway obstruction is caused by enlarged lymphoid tissues within the upper airway, and therefore adenotonsillectomy is considered as the first-line treatment of obstructive sleep apnea in children. Fifty to 70% of patients who have obstructive sleep apnea and treated by surgery are not entirely cured on follow-up polysomnography. In light of this, it is recommended that patients with suspected obstructive sleep apnea undergo a thorough evaluation, and all potential risk factors are identified and treated. The purpose of this review is to familiarize pediatricians with developmental, anatomical, and physiological risk factors involved in the development of obstructive sleep apnea. Additionally, we will present an array of evaluation techniques that can offer adequate assessment of the patient's upper airway anatomy and physiology.
Keywords: upper airway; sleep apnea; sleep breathing; tongue base; snoring; pathophysiology